Effect of counter-face material on the tribological characteristics of UHMW polyethylene under synovial fluid lubrication. (2019) - Hussain, Omar; Ahmad, Babar; Saleem, Shahid; Wani, M.F.; Jebran Khan, M.
Abstract: UHMW polyethylene is widely used for cartilage replacement in joint Arthroplasty. This study is focused on the tribological characteristics of UHMW polyethylene against biomedical grade 316L SS and TiAl6V4 counter-face materials under Synovial fluid lubrication. The Friction Co-efficient and wear rate of the UHMWPE was obtained from the tribological tests performed on the recipro-cating tri-bometer. Lower Friction Co-efficient and specific wear rate was achieved for UHMWPE against TiAl6V4 counter-face material than 316L SS under Synovial fluid lubrication. From the in-vitro tribological tests, it was demonstrated that the UHMWPE/TiAl6V4 is a good tribo-pair for artificial joints.